On Regularized Solution for BBGKY Hierarchy of One-Dimensional Infinite System - Ryabukha, T.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We construct a regularized cumulant (semi-invariant) representation of a solution of the initial value problem for the BBGKY hierarchy for a one-dimensional infinite system of hard spheres interacting via a short-range potential. An existence theorem is proved for the initial data from the space of sequences of bounded functions.